Fetal Mammary Gland Development and Offspring’s Breast Cancer Risk in Adulthood - Lawrence Mabasa; Anri Kotze; Nonhlakanipho F. Sangweni; Tarryn Willmer; Kwazikwakhe B. Gabuza; Oelfah Patel; Sylvester Ifeanyi Omoruyi; Anathi Burns; Rabia Johnson (Biology)
While advancements in early detection and improved access to care have significantly enhanced breast cancer survival rates, the disease remains a significant global malignancy, constituting approximately 12.5% of all new cancer cases and claiming nearly 700,000 lives in 2020. As a result, there is widespread consensus that the most sustainable solution lies in prevention. Indeed, preventive strategies, including lifestyle modifications and research into risk-reducing interventions, offer the potential to address the root causes of noncommunicable diseases such as breast cancer. While conventional wisdom has long attributed established risk factors for breast cancer to age, lifestyle, familial history, and reproductive factors, evidence highlights the maternal environment as a pivotal stage for fetal programming of disease risk, as elucidated in the developmental origins of health and disease (DOHaD) framework. Consequently, a growing body of research has been focused on elucidating epigenomic signatures that influence fetal development while shaping health outcomes and susceptibility to diseases later in life. This review aims to identify fetal mammary developmental genes that have been implicated in breast cancer etiology and the potential interplay of maternal environment in epigenetic programming of breast cancer risk in adulthood.